Teaching assitance and teacher education in higher levels; the intermediate as the space to get nested (Praxis Educativa, 2023)
This paper results from the intersection of two research projects devoted to teacher education processes at a University in Argentina. It wonders about the role of unpaid teaching assistants, specifically in the English Teaching Education Program, in order to explore the value that pre-service teachers recognize in those experiences. Framed under qualitative research and influenced by narrative inquiry, the methodological design includes two recursive steps with focus groups, document analysis, and autoethnographic records. This study uses the resulting polyphony to produce contents that not only narrate the virtues of inhabiting intermediate spaces but also point in the direction of mentorship and guided practice as fruitful instances in the construction of the teacher self in these contexts.
Keywords: higher education; teacher education; subjectivity; unpaid teaching assistants